A Comparative Study of Mechanical Properties of Fly Ash-Based Geopolymer Made by Casted and 3D Printing Methods. (November 2019) - Korniejenko, K; Łach, M; Chou, SY; Lin, WT; Mikuła, J; Mierzwiński, D; Cheng, A; Hebda, M
Abstract: Currently additive manufacturing (AM) is a rapidly developing industrial sector and a disruptive technology. It is an answer for new challenges such as resources saving and energy effectiveness as well as response for circular economy needs. Unfortunately, the full exploitation of 3D printing technology for ceramic is currently limited due to the in-process and in-service performance of the available materials' sets, especially in application in construction industry. The main aim of the article is comparison mechanical properties such as compressive and flexural strength between casted and injected samples (simulation for 3D printing process). The same geopolymer mix, plain as well as with flax fibres, based of fly ash class F was casted and cured in the same temperature prior to its mechanical test with 'printed' samples.